THE INFLUENCE OF ADVERSITY QUOTIENT AND SELF-EFFICACY ON THE TWELVE GRADE MARKETING CLASS STUDENT’S INTEREST IN ENTREPRENEURSHIP AT SMK NEGERI 1 JEMBER - Hadi Sasmito; Mukhamad Zulianto; Sri Wahyuni (Economic Education, University of Jember, 2021)
The purpose of this research was to determine the significant influence of adversity quotient and self-efficacy on the twelve grade marketing class student’s interest in entrepreneurship at SMK Negeri 1 Jember and find the more dominants variable influence students in entreprenuership. The population was students of grade twelve marketing class at SMKN 1 Jember as many as 100 students. Taken simple random sampling technique as many as 51 students. The data collection technique used was a questionnaire method and data analysis techniques performed by multiple linear regression. The result of analysis showed that adversity quotient and self-efficacy has a significant influence on the twelve grade marketing class student’s interest in entrepreneurship at SMK Negeri 1 Jember. F test result is Fcount > Ftable 42,785 > 3,19 with significance level 0,000 < 0,05. The coefficient of determination (R2) equal to 0,641, this show that big precentage influence of adversity quotient and self-efficacy on the twelve grade marketing class student’s interest in entrepreneurship at SMK Negeri 1 Jember is 64,1%, while the rest that is 33,9% influinced by others variable not examined in this research. The results of data analysis regarding the contribution of each variable is adversity quotient of 32,09% and the self-efficacy of 32,01%. This results indicate that nothing is more dominant in influencing interest in entrepreneurship between adversity quotient and self-efficacy. Keywords: Adversity Quotient, Self-Efficacy, Entrepreneurial Intention